2007
DOI: 10.1596/1813-9450-4333
|View full text |Cite
|
Sign up to set email alerts
|

Oil Spills On Other Commodities

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 24 publications
2
48
1
3
Order By: Relevance
“…Gold is also considered as a safe haven in periods of heightened turbulence (Ciner et al, 2013). In agreement with this finding, Baffes (2007) documents lower pass-through from crude oil to prices of precious metals' prices than to prices of other commodities. Further, large swings in precious metals' prices are a source of changes in terms of trade (Aizenman et al, 2012;Pierdzioch et al, 2013), which by turn can trigger changes in the exchange rate (De Gregorio and Wolf, 1994).…”
Section: Return Spilloversmentioning
confidence: 61%
“…Gold is also considered as a safe haven in periods of heightened turbulence (Ciner et al, 2013). In agreement with this finding, Baffes (2007) documents lower pass-through from crude oil to prices of precious metals' prices than to prices of other commodities. Further, large swings in precious metals' prices are a source of changes in terms of trade (Aizenman et al, 2012;Pierdzioch et al, 2013), which by turn can trigger changes in the exchange rate (De Gregorio and Wolf, 1994).…”
Section: Return Spilloversmentioning
confidence: 61%
“…An inflation channel can well explain the theoretical underpinnings between the two assets: rising oil prices usually influence the aggregate price level (Hunt, 2006) and generate inflationary pressures that prompt hedging against inflation in the form of investments in gold (Narayan et al, 2010). Using a long span of annual data , Baffes (2007) shows that the prices of precious metals, including gold, strongly respond to the price of oil. A similar result is produced by Zhang and Wei (2010), who, based on daily data (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008), find that a rising oil price drives up the price of gold, but they do not find a reverse link.…”
Section: Introductionmentioning
confidence: 99%
“…Commodity markets came into prominence after the deep boombust cycle in commodity and oil prices resulting from the great global recession that began at the end of 2007. Several studies have assessed the interrelationship between the oil and commodity prices and some authors have concluded that the relationship is strong while others stated that it is weak (Baffes 2007;Baffes and Haniotis 2010;Pindyck and Rotemberg 1990;Plourde and Watkins 1998). In line with the previous studies, this paper looks at the strength of the relationship.…”
mentioning
confidence: 63%